2017
DOI: 10.1159/000470900
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Tumor-Infiltrating Lymphocytes and the Expression of Topoisomerase IIα in the Prediction of the Clinical Outcome of Patients with Triple-Negative Breast Cancer after Taxane-Anthracycline-Based Neoadjuvant Chemotherapy

Abstract: Purpose: The aim of this study was to determine factors able to predict chemotherapeutic responses and clinical outcomes in patients with triple-negative breast cancer (TNBC) after neoadjuvant chemotherapy (NAC). Methods: Fifty-two TNBC patients on taxane-anthracycline-based NAC were included. The expression of Ki67, topoisomerase IIα (TOPOIIα), and p53, as well as the presence of CD4+ tumor-infiltrating lymphocytes (TILs) and CD8+ TILs were evaluated in biopsy specimens by immunohistochemistry. The expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…BRCA1-IRIS overexpressing (IRISOE) TNBC carcinomas had more CD25 + /Foxp3 + Tregs and few CD8 + /PD-1 + cytotoxic T-cells, which showed that the interaction between macrophages and IRISOE cells initiated an immunosuppressive TME within TNBC tumors [71]. TOPOIIα and CD4 + TILs were significantly positively associated with CD8 + TILs and they exhibited a significantly good 5-year DFS but only a high infiltration of CD8 + TILs showed significantly better 5-year OS in 52 TNBC patients that received taxane-anthracycline-based NAC [103,104]. Calcium/calmodulin-dependent kinase (CaMKK2), expressed in tumor-related stromal cells, could promote tumor growth.…”
Section: Cd8 + Tilsmentioning
confidence: 97%
“…BRCA1-IRIS overexpressing (IRISOE) TNBC carcinomas had more CD25 + /Foxp3 + Tregs and few CD8 + /PD-1 + cytotoxic T-cells, which showed that the interaction between macrophages and IRISOE cells initiated an immunosuppressive TME within TNBC tumors [71]. TOPOIIα and CD4 + TILs were significantly positively associated with CD8 + TILs and they exhibited a significantly good 5-year DFS but only a high infiltration of CD8 + TILs showed significantly better 5-year OS in 52 TNBC patients that received taxane-anthracycline-based NAC [103,104]. Calcium/calmodulin-dependent kinase (CaMKK2), expressed in tumor-related stromal cells, could promote tumor growth.…”
Section: Cd8 + Tilsmentioning
confidence: 97%
“…The same stimuli that activate p53 are likely to activate p73 as well [ 181 ]. If true, then p73 should induce the T-cell death and attenuate their well-documented antitumour effects in nearly all cancer types [ 182 , 183 , 184 ]. Noteworthy, TNFa-induced T-cell apoptosis was dependent on the p73, but not p53 [ 163 ].…”
Section: Tumour-promoting Inflammation and Evading Immune Destructionmentioning
confidence: 99%
“…This is in line with the rationale for an immunomodulatory function of the immune infiltrate and with the prognostic impact we previously discussed. Furthermore, available data also suggests that higher CD8 + /FOXP3 + ratios and high levels of CD4 + and CD8 + TILs are associated with a greater probability of obtaining pCR in eTNBC ( 88 , 96 ). In addition, the presence of TILs both at presentation and in the residual disease after exposure to systemic treatment is associated with a favorable outcome and seems to be inversely related to the activation of the cell proliferation RAS/MAPK pathway ( 88 ).…”
Section: Tils As a Predictive Biomarker In Etnbcmentioning
confidence: 99%